Liquid crystal-polyethylene glycol block copolymer with multi-stimulus response as well as preparation method and application of liquid crystal-polyethylene glycol block copolymer

By combining liquid crystal polymer with polyethylene glycol semi-crystalline polymer, liquid crystal-polyethylene glycol block copolymer is solved, and the problems of low reversible strain and attenuation of shape memory function of existing bidirectional shape memory polymers are solved, and the problem of low reversible strain and attenuation of shape memory function of existing bidirectional shape memory polymers is achieved. Bidirectional shape memory function under multiple stimuli and simplifies the preparation process.

CN119490644AActive Publication Date: 2025-02-21CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411538187.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-21
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing bidirectional shape memory semi-crystalline polymers have less reversible strain, and stress relaxation and de-orientation may occur during multiple actuations, resulting in attenuation of shape memory function.

Method used

Liquid crystal-polyethylene glycol block copolymers are prepared by combining the easily oriented liquid crystal polymer with the polyethylene glycol semicrystalline polymer. The liquid crystal segment plays a role as a physical crosslinking point and anisotropic skeleton. The polyethylene glycol segment acts as a water-absorbing phase and reversible phase. The copolymer is oriented under external force and is fixed through the π-π interaction of the liquid crystal molecular chain to achieve multiple levels. Stimulus response bidirectional shape memory function.

Benefits of technology

It realizes a material with bidirectional shape memory function under the stimulation of temperature, humidity and osmotic pressure. It is simple to prepare, does not require solvents and expensive catalysts, and the material has excellent shape memory effect, is suitable for industrial production and can be processed repeatedly in multiple times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112104340000021
    Figure BDA0005112104340000021
  • Figure BDA0005112104340000022
    Figure BDA0005112104340000022
  • Figure BDA0005112104340000101
    Figure BDA0005112104340000101
Patent Text Reader

Abstract

The invention belongs to the field of shape memory polymers and synthesis and preparation of the shape memory polymers, and discloses a liquid crystal-polyethylene glycol block copolymer with multiple stimulus responses and a preparation method and application of the liquid crystal-polyethylene glycol block copolymer with the multiple stimulus responses. The liquid crystal-polyethylene glycol segmented copolymer is synthesized by directly melting, esterifying and polycondensing a liquid crystal unit, polyethylene glycol and a linking group, then hot-pressing and molding to obtain a thin film with uniform thickness, and stretching and orienting the thin film to obtain a high-molecular intelligent material with multiple stimulation responses. The preparation method does not need a solvent and an expensive catalyst, has no micromolecular monomer residue, can realize clean production, and can realize industrial production by combining various polymer orientation processes such as spinning, film stretching and the like. The oriented liquid crystal chain segment and the polyethylene glycol chain segment can realize a reversible bidirectional shape memory function under the regulation and control of heat, humidity, water and salt solution concentration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of shape memory polymers and their synthesis and preparation, and particularly relates to a liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses such as temperature, humidity and osmotic pressure and a preparation method thereof. Background Art

[0002] Polymer materials have good processability, light weight, softness and corrosion resistance, making them the best choice for smart materials. Among them, polymer materials with two-way shape memory function can imitate human muscles and achieve reversible stretching, bending, tightening or expansion under external stimuli such as heat, light, electricity and magnetism, becoming a hot topic of research at home and abroad.

[0003] Due to the lack of external force-induced oriented crystallization, bidirectional shape memory polymers must introduce internal stress or anisotropic skeletons during the synthesis or preparation process to induce the semi-crystalline polymer to orientate and crystallize during the cooling process, thereby imparting a bidirectional shape memory function. The key to the preparation of existing bidirectional shape memory semi-crystalline polymers is to introduce internal stress or anisotropic skeletons. The fixation of the polymer anisotropic skeleton is mostly achieved by crystallization of high-melting point segments in the polymer. As a result, the crystalline polymer components involved in the reversible strain are relatively small, resulting in a small reversible strain of the bidirectional shape memory semi-crystalline polymer. In addition, the polymer anisotropic skeleton is fixed by crystallization, and during multiple bidirectional shape memory actuations, stress relaxation, deorientation and other phenomena may occur, resulting in the attenuation of the reversible strain. Traditional bidirectional shape memory liquid crystal elastomers are expensive and complex to prepare. In order to obtain an oriented cross-linked structure, most of them require solvents, ultraviolet light, liquid crystal boxes and other reagents and equipment, and it is difficult to reprocess and recycle after oriented cross-linking. This technology replaces some liquid crystal components with cheap polyethylene glycol, and utilizes the matching relationship between liquid crystal polymer and polyethylene glycol crystal structure to promote its oriented crystallization; in addition to maintaining its original thermal response behavior, it also gives it multiple stimulus response modes such as humidity and water. Summary of the invention

[0004] The invention combines a liquid crystal polymer that is easy to orient with a polyethylene glycol semi-crystalline polymer to prepare a liquid crystal-polyethylene glycol block copolymer. The liquid crystal segment plays the role of a physical crosslinking point and an anisotropic skeleton, and the polyethylene glycol segment serves as a water-absorbing phase and a reversible phase. The copolymer molecular chain is oriented under the action of external stretching, and the oriented molecular chain is fixed by the π-π interaction of the orderly benzene ring stacking in the liquid crystal molecular chain. After the block copolymer absorbs water, the polyethylene glycol component anisotropically swells along the orientation direction to obtain an anisotropic hydrogel. Under the stimulation of temperature, humidity and osmotic pressure, the liquid crystal-polyethylene glycol copolymer has a two-way shape memory function.

[0005] The present invention relates to a liquid crystal-polyethylene glycol block copolymer, wherein asymmetric benzene ring side groups are introduced into the liquid crystal block molecular chain of the liquid crystal-polyethylene glycol block copolymer, the molecular chain is arranged in a folded chain manner, and the side group benzene rings are stacked in parallel by dislocation to form a strong π-π interaction, which plays the role of a physical crosslinking point. Polyethylene glycol is introduced into the main chain of the molecular chain of the liquid crystal through molecular design to prepare it into a block form, and it is stretched and oriented in the liquid crystal state. The oriented liquid crystal skeleton is fixed by the ordered benzene ring structure generated in situ, driving the polyethylene glycol chain segment to orient, and giving the copolymer a multi-stimulus response bidirectional shape memory function. 1) Temperature response: The oriented polyethylene glycol molecular chain is crystallized and melted by temperature to make it reversibly retractable along the orientation direction; 2) Humidity response: The oriented molecular chain absorbs moisture in the air and swells anisotropically, and the environmental humidity is adjusted to make it reversibly retractable; 3) Osmotic pressure response: The liquid crystal-polyethylene glycol block copolymer is immersed in water to absorb water and swell, thereby obtaining anisotropic hydrogel. The anisotropically swollen hydrogel is driven to absorb water or dehydrate and shrink by adding salt to adjust the osmotic pressure concentration in water. Compared with traditional shape memory polymer materials, the liquid crystal-polyethylene glycol block copolymer prepared by the present invention has the advantages of simple preparation method and multiple stimulus response.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] 1. The present invention provides a liquid crystal-polyethylene glycol block copolymer, the specific structure of which is as follows:

[0008]

[0009] Where x>50, 1<y<10.

[0010] The liquid crystal-polyethylene glycol block copolymer is randomly composed of the following structural units: [Ⅰ] biphenyldioxanol, [Ⅱ] polyethylene glycol and [Ⅲ] phenylsuccinic acid:

[0011]

[0012] The molar ratio satisfies [I]+[II]=[III], and the mass of [II] accounts for 5 to 50% of the mass of all structural units.

[0013] 2. The present invention provides a method for preparing a liquid crystal-polyethylene glycol block copolymer, wherein the method for preparing a monodomain liquid crystal elastomer comprises the following steps:

[0014] (1) heating and stirring biphenyldioxane, polyethylene glycol and phenylsuccinic acid under the action of a catalyst and under the protection of nitrogen for reaction; then continuing the reaction under vacuum conditions, cooling after the reaction is completed, and obtaining a liquid crystal-polyethylene glycol block copolymer;

[0015] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is made into regular film strips as required, and the strips are stretched and oriented at a certain temperature to obtain liquid crystal-polyethylene glycol block copolymer oriented strips.

[0016] Furthermore, the catalyst described in step (1) is zinc acetate, antimony trioxide, tetrabutyl titanate, stannous octoate, dialkyl tin oxide or antimony glycolate.

[0017] Furthermore, the number average molecular weight Mn of the polyethylene glycol used in step (1) is 1000 to 20000.

[0018] Furthermore, the molar ratio of biphenyldioxanol, polyethylene glycol and phenylsuccinic acid is: n(biphenyldioxanol)+n(polyethylene glycol)=n(phenylsuccinic acid). The mass of polyethylene glycol accounts for 5-50% of the mass of all raw material monomers.

[0019] Furthermore, the number average molecular weight Mn of the liquid crystal-polyethylene glycol block copolymer prepared in step (1) is 20,000 to 100,000.

[0020] Furthermore, in step (1), the heating reaction temperature is 180-220° C., the reaction is carried out for 3 hours, the rotation speed is 60-130 r / min, the vacuum condition is 0-50 Pa, and the reaction is continued for 4 hours.

[0021] Furthermore, in step (2), the liquid crystal-polyethylene glycol block copolymer is heat-pressed into a film at 120°C.

[0022] Furthermore, in step (2), the stretching orientation strain is 300% to 6000%, and the strain is more preferably 500 to 1000%.

[0023] Furthermore, the temperature for stretching and orientation in step (2) is 30 to 80°C, and the preferred orientation temperature is 55°C.

[0024] The prepared liquid crystal-polyethylene glycol block copolymer is used in the preparation of a two-way shape memory product. Specifically, the liquid crystal-polyethylene glycol block copolymer can achieve a reversible two-way shape memory function under the control of temperature, humidity, water and salt solution concentration.

[0025] The present invention also relates to the significance and application of the above-mentioned liquid crystal-polyethylene glycol block copolymer with a main chain block polyethylene glycol, which forms an anisotropic hydrogel after swelling, solves the shortcomings and limitations of the small shape memory change rate of the anisotropic hydrogel, explores a new material and a new preparation method, designs and successfully prepares a new type of fast thermoresponsive liquid crystal-polyethylene glycol block copolymer intelligent material, and successfully prepares a new type of fast linear anisotropic hydrogel.

[0026] Beneficial effects: The present invention provides a liquid crystal-polyethylene glycol block copolymer and a preparation method thereof. Compared with existing liquid crystals and anisotropic hydrogels and their preparation technologies and processes, the present invention has the following advantages: The preparation method of a liquid crystal-polyethylene glycol block copolymer provided by the present invention overcomes the shortcomings and limitations of the traditional preparation method, such as incomplete polymerization reaction and complicated and cumbersome synthesis steps, and does not require solvents and expensive catalysts, and no small molecule monomers will remain in the polymer. The preparation method is simple and easy, and the prepared material has excellent shape memory effect, can be combined with various polymer processing technologies to achieve industrial production, and can be repeatedly processed and reprogrammed. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the structural formula of the liquid crystal-polyethylene glycol block copolymer of the present invention.

[0028] Figure 2 The photographs are of the length change of the sample of Example 6 under temperature stimulation at room temperature and 65°C.

[0029] Figure 3 The following are photos of the anisotropic swelling of the sample of Example 6 in air and water.

[0030] Figure 4 The photographs are of the length changes of the sample of Example 6 in solutions with different ion concentrations.

[0031] Figure 5 The following are photos of the change in strip length of the sample prepared in Example 6 under different humidity conditions.

[0032] Figure 6 The sample prepared in Example 6 was subjected to cycle testing after multiple processing programs.

[0033] Figure 7 The mechanical properties of the sample prepared in Example 6 before and after orientation.

[0034] Figure 8 This is the infrared spectrum of the sample prepared in Example 6. DETAILED DESCRIPTION

[0035] In order to better explain the purpose, technical problems, technical solutions and beneficial effects of the present invention, the above-mentioned parts of the present invention are described and illustrated in more detail below through specific embodiments.

[0036] Example 1

[0037] (1) 4.4450 g (0.0115 mol) of biphenyldioxane, 2.8156 g (0.0145 mol) of phenylsuccinic acid, and 3 g (0.003 mol) of polyethylene glycol with a molecular weight of 1000 were added to a three-necked reaction bottle, and 0.0347 g of antimony trioxide catalyst was added, and the mixture was stirred at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 33,600.

[0038] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching strain of 500%, thereby obtaining a liquid crystal-polyethylene glycol block copolymer.

[0039] Example 2

[0040] (1) 2.8293 g (0.00732 mol) of biphenyldioxane, 2.3923 g (0.01232 mol) of phenylsuccinic acid, and 5 g (0.005 mol) of polyethylene glycol with a molecular weight of 1000 were added to a three-necked reaction bottle, and 0.0277 g of zinc acetate as a catalyst was added, and stirred at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced, and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 10,000.

[0041] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching strain of 700%, thereby obtaining a liquid crystal-polyethylene glycol block copolymer.

[0042] Example 3

[0043] (1) 4.8895 g (0.01265 mol) of biphenyldioxane, 3.4273 g (0.01765 mol) of phenylsuccinic acid, and 2 g (0.005 mol) of polyethylene glycol with a molecular weight of 4000 were added to a three-necked reaction bottle, and 0.0277 g of zinc acetate catalyst was added, and the mixture was stirred at 180° C. for 3 hours under the protection of nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 33,600.

[0044] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 1700% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0045] Example 4

[0046] (1) 4.0198 g (0.0104 mol) of biphenyldioxane, 2.2137 g (0.0114 mol) of phenylsuccinic acid, and 4 g (0.001 mol) of polyethylene glycol with a molecular weight of 4000 were added to a three-necked reaction bottle, and 0.0361 g of zinc acetate catalyst was added, and the mixture was stirred and reacted at 180° C. for 3 hours under the protection of nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 21600.

[0047] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 1200% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0048] Example 5

[0049] (1) 4.7542 g (0.0123 mol) of biphenyldioxane, 2.4855 g (0.0128 mol) of phenylsuccinic acid, and 3 g (0.0005 mol) of polyethylene glycol with a molecular weight of 6000 were added to a three-necked reaction bottle, and 0.0417 g of stannous octoate as a catalyst was added, and the mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 37,900.

[0050] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 300%, thereby obtaining a liquid crystal-polyethylene glycol block copolymer.

[0051] Example 6

[0052] (1) 3.3434 g (0.00865 mol) of biphenyldioxane, 1.8408 g (0.00948 mol) of phenylsuccinic acid, and 5 g (0.00083 mol) of polyethylene glycol with a molecular weight of 6000 were added to a three-necked reaction bottle, and 0.0386 g of stannous octoate as a catalyst was added, and the mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 36,900.

[0053] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 2200% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0054] Example 7

[0055] (1) 5.4886 g (0.0142 mol) of biphenyldioxane, 2.8059 g (0.01445 mol) of phenylsuccinic acid, and 2 g (0.00025 mol) of polyethylene glycol with a molecular weight of 8000 were added to a three-necked reaction bottle, and 0.0419 g of dialkyltin oxide as a catalyst was added. The mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. A vacuum was then introduced, and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 42,700.

[0056] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 3600% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0057] Example 8

[0058] (1) 4.0701 g (0.01053 mol) of biphenyldioxane, 2.1418 g (0.01103 mol) of phenylsuccinic acid, and 4 g (0.0005 mol) of polyethylene glycol with a molecular weight of 8000 were added to a three-necked reaction bottle, and 0.0426 g of dialkyltin oxide as a catalyst was added. The mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 43,900.

[0059] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 1500% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0060] Example 9

[0061] (1) 6.18432 g (0.0160 mol) of biphenyldioxane, 3.1263 g (0.0161 mol) of phenylsuccinic acid, and 1 g (0.0001 mol) of polyethylene glycol with a molecular weight of 10,000 were added to a three-necked reaction bottle, and 0.0419 g of catalyst antimony glycol was added, and stirred at 180° C. for 3 hours under the protection of nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 62,200.

[0062] (3) The liquid crystal-polyethylene glycol block copolymer obtained in step (2) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 1800% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0063] Example 10

[0064] (1) 4.7928 g (0.0124 mol) of biphenyldioxane, 2.4661 g (0.0127 mol) of phenylsuccinic acid, and 3 g (0.0003 mol) of polyethylene glycol with a molecular weight of 10,000 were added to a three-necked reaction bottle, and 0.0423 g of ethylene glycol antimony catalyst was added. The mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 39,900.

[0065] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 2100% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0066] Embodiment 11

[0067] (1) 6.1843 g (0.0160 mol) of biphenyldioxane, 3.1199 g (0.016067 mol) of phenylsuccinic acid, and 1 g (0.000067 mol) of polyethylene glycol with a molecular weight of 15,000 were added to a three-necked reaction bottle, and 0.0435 g of catalyst antimony glycol was added, and the mixture was stirred at 200° C. for 3 hours under the protection of nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 85,100.

[0068] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 5000% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0069] Example 12

[0070] (1) 4.7928 g (0.0124 mol) of biphenyldioxane, 2.4467 g (0.0126 mol) of phenylsuccinic acid, and 3 g (0.0002 mol) of polyethylene glycol with a molecular weight of 15,000 were added to a three-necked reaction bottle, and 0.0451 g of antimony trioxide as a catalyst was added, and the mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 73,300.

[0071] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 3000% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0072] Embodiment 13

[0073] (1) 6.5322 g (0.0169 mol) of biphenyldioxane, 3.2865 g (0.016925 mol) of phenylsuccinic acid, and 0.5 g (0.000025 mol) of polyethylene glycol with a molecular weight of 20,000 were added to a three-necked reaction bottle, and 0.0397 g of antimony trioxide as a catalyst was added, and the mixture was stirred at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 85,100.

[0074] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 6000% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0075] Embodiment 14

[0076] (1) 5.4886 g (0.0142 mol) of biphenyldioxane, 2.7768 g (0.0143 mol) of phenylsuccinic acid, and 2 g (0.0001 mol) of polyethylene glycol with a molecular weight of 20,000 were added to a three-necked reaction bottle, and 0.0417 g of antimony trioxide as a catalyst was added, and the mixture was stirred and reacted at 180° C. for 3 hours under the protection of a nitrogen atmosphere. Then, vacuum was introduced and the reaction was continued at 180° C. and 30 Pa for 4 hours. After the reaction was completed, the mixture was cooled to obtain a liquid crystal-polyethylene glycol block copolymer with a number average molecular weight of 100,000.

[0077] (2) The liquid crystal-polyethylene glycol block copolymer obtained in step (1) is hot-pressed at 120° C. into a uniform film with a thickness of 0.4 mm, cut into strips with a width of 4 mm, and stretched and oriented on a hot plate at 55° C. with a stretching ratio of 3500% to obtain a liquid crystal-polyethylene glycol block copolymer.

[0078] Embodiment 15

[0079] The difference between Example 15 and Example 5 is that the polyethylene glycol with a molecular weight of 6000 is replaced by polyethylene glycol with a molecular weight of 8000. The other operations are the same as those in Example 5 to prepare a liquid crystal-polyethylene glycol block copolymer.

[0080] Example 16

[0081] The difference between Example 16 and Example 5 is that the polyethylene glycol with a molecular weight of 6000 is replaced by polyethylene glycol with a molecular weight of 10000, and the other operations are the same as those in Example 5 to prepare a liquid crystal-polyethylene glycol block copolymer.

[0082] Embodiment 17

[0083] The difference between Example 17 and Example 5 is that the polyethylene glycol with a molecular weight of 6000 is replaced by polyethylene glycol with a molecular weight of 5000. The other operations are the same as those in Example 5 to prepare a liquid crystal-polyethylene glycol block copolymer.

[0084] Embodiment 18

[0085] The difference between Example 18 and Example 5 is that the polyethylene glycol with a molecular weight of 6000 is replaced by polyethylene glycol with a molecular weight of 4000. The other operations are the same as those in Example 5 to prepare a liquid crystal-polyethylene glycol block copolymer.

[0086] Embodiment 19

[0087] Compared with Example 5, Example 19 differs in that: in step (2), the strips are stretched and oriented, and the stretching ratio is replaced by 500% instead of 300%, and other operations are the same as Example 5, to prepare a liquid crystal-polyethylene glycol block copolymer.

[0088] Embodiment 20

[0089] Compared with Example 5, Example 20 differs in that: in step (2), the strips are stretched and oriented, and the stretching ratio is replaced by 800% instead of 300%, and other operations are the same as Example 5, to prepare a liquid crystal-polyethylene glycol block copolymer.

[0090] Embodiment 21

[0091] Compared with Example 5, Example 21 differs in that: in step (2), the strips are stretched and oriented, and the stretching ratio is replaced by 1500% instead of 300%, and other operations are the same as Example 5, to prepare a liquid crystal-polyethylene glycol block copolymer.

[0092] Embodiment 22

[0093] The difference between Example 22 and Example 5 is that in step (2), the strips are stretched and oriented, and the stretching ratio is replaced by 3000% instead of 300%, and the other operations are the same as those in Example 5, and a liquid crystal-polyethylene glycol block copolymer is prepared.

[0094] The liquid crystal-polyethylene glycol block copolymer film test strips prepared in Examples 1-22 were tested for temperature-induced reversible deformation rate, anisotropic swelling deformation rate, anisotropic change rate of 2M and 0M K2CO3 concentration samples, and anisotropic change rate between 20% and 90% relative humidity. The test results are recorded in Table 1.

[0095] Table 1 Deformation of anisotropic hydrogels in different embodiments (due to the slight difference of each actuator, the error in the following table is ±5%)

[0096]

[0097]

[0098] In Table 1, the reversible deformation is calculated by the following formula:

[0099] Temperature-induced reversible deformation rate = (L1-L0) / L0×100%, wherein L0 is the length of the anisotropic hydrogel strip after being placed at high temperature (65°C) for 1 minute; L1 is the length of the anisotropic hydrogel strip after being placed at low temperature (25°C) for 1 minute.

[0100] Anisotropic swelling deformation rate = (L1-L0) / L0×100%, wherein L0 is the length of the anisotropic hydrogel strip after being placed in air for 10 minutes; L1 is the length of the anisotropic hydrogel strip after being placed in water for 10 minutes.

[0101] The anisotropy change rate of 2M and 0M K2CO3 concentration samples = (L1-L0) / L0×100%, wherein L0 is the length of the anisotropic hydrogel sample after being placed in a 2M concentration K2CO3 solution for 10 minutes; L1 is the length of the anisotropic hydrogel sample after being placed in a 0M concentration K2CO3 solution for 10 minutes.

[0102] Anisotropy change rate between 20% and 90% relative humidity = (L1-L0) / L0×100%, wherein L0 is the length of the anisotropic hydrogel strip after being placed in air at RH=20 for 10 minutes; L1 is the length of the anisotropic hydrogel strip after being placed in air at RH=90 for 10 minutes.

[0103] From Table 1, it can be seen that too high or too low PEG molecular weight will have an adverse effect on the anisotropic swelling of the brake and the response to ions and humidity. The optimal range of PEG molecular weight is Mn = 6000-10000. The optimal stretching ratio is 800%, and too high or too low stretching ratio will have an adverse effect on various response properties of the brake.

[0104] Figure 6 This is the cyclic test result of the sample prepared in Example 6 after multiple processing and programming. It shows the cyclic condition of temperature-induced reversible deformation, anisotropic swelling, ion response and humidity response. Compared with the condition before repeated processing, the temperature response of the brake obtained by re-programming after multiple processing is basically not affected (from 27% to 25% within the error range).

[0105] Figure 7 The mechanical properties of the samples prepared in Example 6 before and after orientation are shown in Figure 6. Figure 7 Left is forward, Figure 7 Right is after orientation, from Figure 7 Orientation can be obtained to significantly improve the breaking strength of the brake.

[0106] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses, characterized in that: The specific structure of the copolymer is as follows: Where x>50, 1<y<10.

2. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 1, characterized in that: The liquid crystal-polyethylene glycol block copolymer is prepared by reacting the structural unit [Ⅰ] liquid crystal primitive, polyethylene glycol [Ⅱ] and the connecting group random unit [Ⅲ]: The molar ratio satisfies [I]+[II]=[III], and the mass of [II] accounts for 5 to 50% of all structural units.

3. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 2, characterized in that: The preparation method of the liquid crystal-polyethylene glycol block copolymer comprises the following steps: (1) heating and stirring biphenyldioxane, polyethylene glycol and phenylsuccinic acid under the protection of a catalyst and nitrogen for reaction; the system after the reaction continues to react under vacuum conditions, and after the reaction is completed, cooling is performed to obtain a liquid crystal-polyethylene glycol block copolymer; (2) Forming the liquid crystal-polyethylene glycol block copolymer obtained in step (1) into a film, stretching and orienting the film at a certain temperature, wherein the stretching orientation strain is 300% to 6000%, thereby obtaining a liquid crystal-polyethylene glycol block copolymer oriented material.

4. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 3, characterized in that: The catalyst described in step (1) is zinc acetate, antimony trioxide, tetrabutyl titanate, stannous octoate, dialkyl tin oxide or antimony glycol; the heating reaction temperature is 180-220°C.

5. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 3, characterized in that: The number average molecular weight Mn of the polyethylene glycol used in step (1) is 1000 to 20000.

6. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 5, characterized in that: The number average molecular weight Mn of polyethylene glycol is 4,000 to 10,000.

7. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 3, characterized in that: The stretching orientation strain in step (2) is 500 to 1000%.

8. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 3, characterized in that: The number average molecular weight Mn of the liquid crystal-polyethylene glycol block copolymer prepared in step (2) is 10,000 to 100,000.

9. The method for preparing the liquid crystal-polyethylene glycol block copolymer having multiple stimulus responses according to claim 3, characterized in that: The temperature for stretching and orientation in step (3) is 30 to 80°C.

10. Use of a liquid crystal-polyethylene glycol block copolymer prepared according to the method of any one of claims 2 to 9 in the preparation of a two-way shape memory product, characterized in that: Liquid crystal-polyethylene glycol block copolymers can achieve reversible bidirectional shape memory function under the regulation of temperature, air humidity, water and salt solution concentration.

Citation Information

Patent Citations

  • High polymer material with two-way shape memory effect and preparation method thereof

    CN105802196A

  • PP(polypropylene) / liquid crystal polymer composite with high beta-form crystal content and preparation method

    CN106397987A

  • Main chain type liquid crystal elastomer with lateral groups containing cinnamyl cross-linking monomers and preparation method of main chain type liquid crystal elastomer

    CN109485837A